Key Clinical Topics in Sports and Exercise Medicine - Narvani, A. A. A. Ali; Thomas, P. Panos; Lynn, B. Bruce (Key Clinical Topics, 2014)
This book aims to provide sports physicians, general practitioners, physiotherapists, orthopaedic surgeons and all those involved in the medical care of athletes with a quick reference on sports and exercise medicine. Sports and exercise medicine is a hugely rewarding specialty and it helps the individuals to be active and healthy. It helps to prevent injury and also helps the injured individuals to get back to full fitness as quickly as possible. Each section covers the injuries in sports with its clinical features, investigations, management and the duration required to return to sports. Patients with chronic conditions have been encouraged to enhance their recovery and decrease the burden of their disorder by regular exercise. Physical activity has rightly been promoted as an effective way of preventing chronic and debilitating diseases, as well as improving quality of life. As the individuals with disabilities are participating in sports, it is essential to give them appropriate advice and guidelines in choosing the right sport that meet their needs and abilities. A good knowledge on sports injuries can help a physician to minimise the injury and create a stable environment for a better lifestyle.